The software instrumen for gymnast posture analysis - Aji-Putra, R. B.; Rahayu, T.; Kasmini, W.; Sulaiman (Journal of Human Sport & Exercise, 2022)
The general aim of this research was to develop an ideal instrument to analysethe ideal anthropometric posture of artistic gymnastic sports so that profiles and proportions of the length of the athletes were ideal through analysis images. Research and development methods used the following paths for problem identification, information gathering, product design, design validation, product testing, trial used and mass product manufacturing. The results of the study contain software design (UNG) with the performance of storing and analysing images by adjusting the real coordinate scale and height digital scale as a reference to measure the athlete's body length and the degree of posture imbalance. Validity was measured in two ways, namely correlating the standard length gauge No. Reg C4 / VI / 250419 with measurements in the software amounting to 0.92 very high categories and averaging in hundreds of assessments of 92 ICT experts and sports experts at 96.5. Reliability using retest was .95 very high category. Posture Image Analysis of 150 male world gymnasts All the figures around depict the average height, Percentage of limb length, posture imbalance. in degree, posture analysis which is suitable and efficient in displaying for each exercise.it describe an average height of 166 cm with a leg length proportion of 54%, Body 26%, Head 13% and neck 5%. The conclusion of UNG software was to effectively analysethe profile image of the sample male artistic gymnastic ideal to produce a profile and the length of anthropometric proportions of the athlete's body members in accordance with the actual object